Latin America and Social Solidarity Economy Legislation - Heras Monner Sans, Ana Ines (2014)
Anthropology contributes to an important debate on otra economía & sociedad by making visible what and how are things accomplished, day-to-day, and what may these practices mean. I portrayed how? For example? When we want to interpret educational emancipatory school processes, we need to understand more closely what kinds of practices take place, who and how frame these practices, and in which ways are they challenging the system that is being critiqued. The same applies to other areas that are framed and seen as part of this other paradigm (e.g., barter exchange, community currency, gift-exchange, community and popular culture, folk art). However, it is also true that normative and legislative aspects are also important if we want to understand how social solidarity economy is being enacted in Latin America. My point is that good anthropology needs to refer to socio-political and legal-jurisprudence frameworks, in as much as good policy decision makers, public servants and legislators may benefit from understanding what anthropology has to say about how people actually do things daily.